Seasonal difference in bone characteristics and body composition of elite speed skaters - Varley, I.; Greeves, J. P.; Sale, C. (International Journal of Sports Medicine, 2019)
We investigated the changes in bone characteristics and body composition of elite speed skaters across two competitive seasons. Twelve elite speed skaters (age 23±4 years; height 1.73±0.09 m; body mass 68.5±8.8 kg; mean±1 SD) were assessed by DXA and pQCT for Bone Mineral Density (BMD), Bone Mineral Content (BMC), area, bone strength, cortical thickness and density at four points over the course of four competitive seasons. Body composition data was also collected. A main effect of time was shown for whole body BMC, right leg BMC, and trabecular area (P<0.05). Whole body BMC was higher during pre-season and end of season in comparison to mid-season (1.0%, P=0.007; 0.8%, P=0.017), right leg BMC was higher at the pre-season scan in comparison to the post pre-season scan (1.8%,P=0.020) and trabecular area was higher during the mid-season and end of season when compared to the pre-season (1.4%, P=0.012; 1.0%, P=0.003). Seasonal changes in bone characteristics and body composition are shown in elite speed skaters over a competitive season. The changes are thought to be a result of fluctuations in training load. These data may have implications for training design and injury risk management in elite sport.